Um estudo sobre o uso das mídias sociais como ferramenta de negócios e seus impactos no comportamento do consumidor - Oliveira, Cássia Ferreira (Brasil, 2021)
With the evolution of technology, communication and the emergence of electronic commerce, the way in which people seek to maintain an ever closer and more attractive contact between companies and customers has transformed social media as the main strategic means of doing business. In this context, the aim of this study is to analyze how social media are used by companies to create new strategies in order to boost their business and attract customers, and how it is possible to influence consumer behavior through existing digital tools. The methodology adopted to carry out this research is divided into Systematic Mapping and Opinion Survey, through the application of a questionnaire to entrepreneurs in Itacoatiara/AM. With the results obtained, it is possible to see the importance of social media for companies, which they consider to be a potential business tool today.